Influence of junior high school students’ knowledge, attitudes, and practices on earthquake and tsunami preparedness simulations in Padang - Yulfiwanti Idha; Mayetti; Ihsan Indra (E3S Web of Conferences)
Padang, a city highly susceptible to earthquakes and tsunamis, requires students to possess adequate knowledge and develop cautious behaviors when confronted with such calamities. This study seeks to evaluate the influence of earthquake and tsunami simulations on junior high school students’ learning, perspectives, and practices. A pretest-posttest experimental design was used, involving eighth and ninth- grade students from SMP Negeri 4 Padang. The simulation exercises included earthquake and tsunami disaster drills. Data was collected through observation, focusing on the learning process and the school’s preparedness, including evacuation route planning. Of 87 respondents, 42 (48.3%) were male, and 45 (51.7%) were female. The age distribution was as follows: 2 students (2.3%) were 12 years old, 33 (31%) were 13, 48 (50.6%) were 14, and 15 (16.1%) were 15 years old. The simulations substantially improved students’ understanding, attitudes, and behaviors in dealing with earthquakes and tsunamis (p < 0.05). The earthquake and tsunami simulations at SMP Negeri 4 Padang effectively enhanced students’ knowledge, attitudes, and disaster preparedness. The drills improved their awareness and response to emergencies, particularly in following evacuation procedures. This hands-on approach solidified their theoretical understanding and fostered a proactive mindset towards disaster management.